Code-switching and Use of Other Languages by Students in the Spanish L2 Language Classroom (BEOIBERÍSTICA - Journal of Iberian, Latin American and Comparative Studies (ISSN: 2560-4163 Online), 2017)
The paper discusses the results of observations centered on students’ code-switching in Spanish classes. Concerning the definition of a bilingual and the multilingual person, we consider it should be based on a broad perspective, defined by sociolinguistics. The observations took place in a public center for adult education in Spain, in November 2016.The effectiveness of the use of L1 in L2 or FL classes is a subject extensively discussed among researchers and teachers. Here we present some of the work centered on this subject in the context of teaching different languages, Spanish in particular.We consider that this use can be effective both in teaching and learning the TL, but we are also aware of its potential inconvenience in case it is not developed in a strategic manner. Research is needed in order to define which strategies of use of L1, and other languages, are appropriate and beneficial for teaching and learning L2 and FL.Key words: teaching Spanish, code-switching, bilingualism, multilingualism.